Immunomodulation Induced During Interferon-α Therapy Impairs the Anti-HBV Immune Response Through CD24+CD38hi B Cells - Fu, Binqing; Wang, Dongyao; Shen, Xiaokun; Guo, Chuang; Liu, Yanyan; Ye, Ying; Sun, Rui; Li, Jiabin; Tian, Zhigang; Wei, Haiming (Frontiers in Immunology, 2020)
Type 1 interferon is widely used for antiviral therapy, yet has yielded disappointing results toward chronic HBV infection. Here we identify that Peg-IFNα therapy towards persistent infection in humans is a double-edged sword of both immunostimulation and immunomodulation. Our studies of this randomised trial showed persistent Peg-IFNα therapy induced large number of CD24+CD38hi B cells and launched a CD24+CD38hi B cells centered immunosuppressive response, including downregulating functions of T cells and NK cells. Patients with low induced CD24+CD38hi B cells have achieved an improved therapeutic effect. Specifically, using the anti-CD24 antibody to deplete CD24+CD38hi B cells without harming other B cell subsets suggest a promising strategy to improve the therapeutic effects. Our findings show that Peg-IFNα therapy towards persistent infection constitutes an immunomodulation effect, and strategies to identifying the molecular basis for the antiviral versus immunomodulatory effects of IFNα to selectively manipulate these opposing activities provide an opportunity to ameliorate anti-virus immunity and control viral infection.